2007
DOI: 10.2174/157341107779314262
|View full text |Cite
|
Sign up to set email alerts
|

Solution-State NMR Experiments Based on Heteronuclear Cross-Polarization

Abstract: Heteronuclear coherence transfer in liquid-state NMR applications has been traditionally performed using pulse-interrupted delay schemes such as INEPT-type pulse trains. So far, the alternative use of heteronuclear crosspolarization (HCP) has only been limited to a few cases involving exclusively in-phase to in-phase transfers. In this revision work a theoretical description on the effect and the characteristic anisotropic features of HCP is introduced in terms of product operator formalism. A very intuitive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 78 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…14 Furthermore, multiple CP schemes including MLEV, 26,27 DIPSI, 28 WALTZ 29 have been developed to alleviate the aforementioned inhomogeneity and heating-derived problems. 17,18,[30][31][32][33][34] Still, even these schemes become inefficient when the exchange rate 𝑘 đ»đ‘Š of the H N with water, exceeds ≈10J. The reasons for this are not immediately evident, considering that abundant solvent water protons H water are constantly repolarizing the H N bound to the 15 N. Furthermore, the relatively long spin relaxation times of 15 N (and 13 C) in such systems, 35,36 could enable principles akin to those used in the recently proposed Looped, projected spectroscopy (L-PROSY) 37 experiment, to improve these heteronuclear transfers even in fast chemical exchange cases.…”
Section: Introductionmentioning
confidence: 99%
“…14 Furthermore, multiple CP schemes including MLEV, 26,27 DIPSI, 28 WALTZ 29 have been developed to alleviate the aforementioned inhomogeneity and heating-derived problems. 17,18,[30][31][32][33][34] Still, even these schemes become inefficient when the exchange rate 𝑘 đ»đ‘Š of the H N with water, exceeds ≈10J. The reasons for this are not immediately evident, considering that abundant solvent water protons H water are constantly repolarizing the H N bound to the 15 N. Furthermore, the relatively long spin relaxation times of 15 N (and 13 C) in such systems, 35,36 could enable principles akin to those used in the recently proposed Looped, projected spectroscopy (L-PROSY) 37 experiment, to improve these heteronuclear transfers even in fast chemical exchange cases.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to DEPT and INEPT, heteronuclear cross-polarization (HCP) may be used to enhance the sensitivity of 13 C NMR experiments. Although HCP has been widely employed in solid-state NMR, it has only recently gained popularity in liquid-state applications. , …”
Section: Resultsmentioning
confidence: 99%
“…Recent progress in NMR spectroscopy, including the exploitation of amide‐proton and water magnetization under conditions under which only the amide protons are excited, as well as direct carbon‐atom detection, has made it possible record NMR spectra of biomolecules under near‐physiological conditions of temperature and pH value . At around the same time, Yuwen and Skrynnikov showed that the initial INEPT transfer in a standard 1 H, 15 N HSQC pulse sequence could be advantageously replaced by a J‐cross‐polarization (J‐CP) transfer, since this excitation mechanism uses the large water‐magnetization reservoir to continuously replenish the amide‐proton magnetization . Herein, we describe the combination of both approaches—J‐CP excitation and CO detection—and present an improved NMR experiment that enables an N‐CO spectrum to be recorded under truly mammalian physiological conditions, that is, at 37 °C and pH 7.4.…”
Section: Figurementioning
confidence: 99%